STRATEGI PEMANFAATAN POTENSI EKONOMI DESA MELALUI BUMDes DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI DESA LABUH AIR PANDAN KECAMATAN MENDO BARAT KABUPATEN BANGKA - Sujana, Tatang; Fikri, Zakiyudin (Universitas Panca Marga, 2023)
The research arises on the basis of problems that often occur. In this case the existence of BUMDes has a very important role for the community. BUMDes is a vehicle to be able to manage all the potential owned by the village. Therefore, a professional management strategy is needed so that the benefits received by the community become more optimal. This research wants to examine how the Labuh Air Pandan Village strategy manages the village's economic potential through BUMDes using descriptive qualitative methods. This research uses primary and secondary data, namely interviews, observation and documentation. Analysis using triangulation techniques, namely data reduction, data presentation, conclusion drawing. Based on the results of the research, the author concludes that the strategy in optimizing the economic potential of the village through BUMDes in Labuh Air Pandan Village, it can be concluded that the strategy that has been carried out is generally good but not optimal. This is because of several strategic indicators used in examining these problems, there are still weaknesses, namely in the utilization strategy and the strategy of using information technology.